Implied gravity promotes coherent motion perception - Xiqian Lu; Bogeng Song; Shaoshuai Zhang; Shujia Zhang; Mei Huang; Ying Wang; Yi Jiang (npj Microgravity)
Abstract Gravity, a constant in Earth’s environment, constrains not only physical motion but also our estimation of motion trajectories. Early studies show that natural gravitational acceleration facilitates the manual interception of free-falling objects. However, whether implied gravity affects the perception of coherent motion patterns from local motion cues remains poorly understood. Here, we designed a motion coherence threshold task to measure the visual discrimination of coherent global motion with natural (1 g) and reversed (−1 g) gravitational accelerations. Across five experiments, we showed that the perceptual thresholds of motion coherence were significantly lower under the natural gravity than the reversed gravity condition, regardless of variations in stimulus parameters and visual contexts. These convergent results suggest that the human visual system inherently extracts the gravitational acceleration cues conveyed by local motion signals and integrates them into a unified global motion, thereby facilitating the visual perception of complex motion patterns in natural environments.